The moderating effect of change agent and organizational climate on the total quality management and organisational sustainability in Saudi Arabia hotel industry - Alharbi, Khalid (2016)
Saudi hotel industry still has not performed to their fullest potential. The industry has to focus on quality improvement efforts to improve their performance. Therefore, this study is undertaken to examine the impact of total quality management (TQM) practices on the sustainability of the Saudi hotel industry. It also aims to investigate the moderating effect of change agent and organisational climate on the total quality management (TQM) practices-sustainability relationship of the Saudi hotel industry. This study was motivated by the inconsistency of findings reported in the literature regarding the relationship of total quality management practices, change agent and organisational climate variables, with sustainability. Such inconsistencies have led to the emergence of a new research stream that recommended the investigation of the moderating variables that could contribute to the aforementioned relations between variables. In the present study, different theories were employed including the social exchange theory and the resource-based view theory, to provide an insight into the relationships among variables in the proposed conceptual framework. The study involved survey questionnaire which were randomly distributed to 932 hotels in five cities of Saudi. Out of the total number of retrieved questionnaires (238), 204 were usable for analysis. The researcher employed correlation and hierarchical regression analysis to analyze the study variables indirect and direct relationships. The results show a positive relationship between the TQM and the organisational sustainability, and they support the moderating effects of both change agent and organisational climate on the TQM-organisational sustainability relationship. The study is concluded by providing managerial, policy and theoretical implications as well as recommendations for future studies.